Early Warning System Berbasis Internet Of Things (IOT) pada Daerah Rawan Bencana Banjir di Kota Semarang - Sari, Putri Novita; Christanto, Febrian Wahyu (Politeknik Negeri Batam, 2023)
Semarang is a city that often experiences flooding. One of the causes of frequent flooding in Semarang City is land subsidence. The rise in sea water in Semarang is currently reaching 3-5 millimeters per year while land subsidence is reaching 9 cm. Land subsidence in the city is 30 times greater than global sea level rise. This land subsidence causes the city of Semarang to often be hit by floods during high rainfall because the land position on the coast is lower than sea level water. Efforts to anticipate floods include creating an early flood detection system. This flood height detector aims to describe the status of the water level when the water level has reached the maximum level. This flood detection system uses a water level sensor to detect water levels, a NodeMCU ESP8266 to read data and send it via the internet, as well as a buzzer which functions to make a sound when the sensor detects water and has the potential for a flood disaster. The system will work automatically when water hits the sensor by sending flood detection status information via the Blynk application on a smartphone. This technology aims to provide early notification of a flood for public safety. It was found that the average value of user satisfaction reached 75% when testing the prototype results from this study and the accuracy value of prototype testing reached 100%.